2021
DOI: 10.48550/arxiv.2111.12983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of domain gap problem in several deep-learning-based CT metal artefact reduction methods

Abstract: Metal artefacts in CT images may disrupt image quality and interfere with diagnosis. Recently many deep-learning-based CT metal artefact reduction (MAR) methods have been proposed. Current deep MAR methods may be troubled with domain gap problem, where methods trained on simulated data cannot perform well on practical data. In this work, we experimentally investigate two image-domain supervised methods, two dual-domain supervised methods and two image-domain unsupervised methods on a dental dataset and a torso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the case of medical images, these kind of data are hard to create. Because of that, the majority of learning-based methods are forced to use simulated data, although they oftentimes cannot completely reproduce the complex underlying physical image formation process (e.g., DeepDRR 26 ), thus ending up with a domain gap as described by Du et al 27 Alternatively, physically correct simulations require extensive computational effort in the case of, for example, Monte Carlo simulations (e.g., MC-GPU 28 ). We assume that methods, which are solely trained on simulated data, do struggle to generalize well for a variety of real clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of medical images, these kind of data are hard to create. Because of that, the majority of learning-based methods are forced to use simulated data, although they oftentimes cannot completely reproduce the complex underlying physical image formation process (e.g., DeepDRR 26 ), thus ending up with a domain gap as described by Du et al 27 Alternatively, physically correct simulations require extensive computational effort in the case of, for example, Monte Carlo simulations (e.g., MC-GPU 28 ). We assume that methods, which are solely trained on simulated data, do struggle to generalize well for a variety of real clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…And the presented PISC method yields the optimal MAR performance in terms of more structure preservation and higher spatial resolution. Therefore, the presented PISC method can avoid the domain gap problem, which commonly exists in the DL based MAR methods (Du et al 2021). The main reason is the presented PISC method could leverage the latent structure information in raw projection data to recover the structural details near the metal implants.…”
Section: Comparison With DL Based Mar Methodsmentioning
confidence: 99%
“…The main limitation with SI approach is inaccurate segmentation problem that usually appear as undersegmentation and over-segmentation of metal trace within the sinogram or projection data (18). In our previous studies, it has also been reported that the artifacts were not completely removed, or additional artifacts may be introduced due to incomplete interpolation of the projection data or sinogram (27)(28).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, deep learning-based algorithm (deep MAR) has been proposed which is either applied on projection (DLP-MAR) or image (DLI-MAR) domains, or combinations of both domains known as dual-domain MAR (17)(18)(19)(20). The deep MAR methods trained the deep network using both real and simulated datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation